2010
DOI: 10.1063/1.3432198
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic signatures of proton transfer dynamics in the water dimer cation

Abstract: Using full dimensional EOM-IP-CCSD/aug-cc-pVTZ potential energy surfaces, the photoelectron spectrum, vibrational structure, and ionization dynamics of the water dimer radical cation, (H 2 O) + 2 , were computed. We also report an experimental photoelectron spectrum which is derived from photoionization efficiency mea- Hamiltonian was used to compute the ionization dynamics for both the ground state and first excited state of the cation. The dynamics show markedly different behavior and spectroscopic signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
139
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(155 citation statements)
references
References 60 publications
10
139
6
Order By: Relevance
“…34,35 Finally we discuss the nature of the excitation process that is occurring in these mixed 16 The protonated cluster appearance energies agree well with those measured earlier 2 but the photoionization efficiency curve follows the shape of the argon cluster absorption spectrum quite dramatically. This is reflected in the enhancement of signal around 11.5 eV, peaking at 11.92 eV, dropping down and then rising again.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…34,35 Finally we discuss the nature of the excitation process that is occurring in these mixed 16 The protonated cluster appearance energies agree well with those measured earlier 2 but the photoionization efficiency curve follows the shape of the argon cluster absorption spectrum quite dramatically. This is reflected in the enhancement of signal around 11.5 eV, peaking at 11.92 eV, dropping down and then rising again.…”
supporting
confidence: 74%
“…4 Theory has shown that the structure of the water cluster ions are very different from their neutral ground state geometries, and gives rise to poor Franck-Condon (FC) factors, leading to a vibrationally excited cluster ion upon vertical excitation. 4,16,[36][37][38] This vibrationally excited cluster ion will rearrange via proton transfer to form a complex of the form (H 3 O) + OH in the case of the dimer, and it is stable to dissociation at threshold. Indeed, the non-fragmented dimer has been observed in photoionization experiments, 16,39 where at the appearance of (H 3 O) + at 11.71 eV is reflected directly in a lowering of signal of (H 2 O) 2 + .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This method has been successfully applied to describe electronic structure of ionized benzene dimers [31,33], water clusters [34][35][36] and dimers of nucleobases [3-5, 7, 8].…”
Section: A Electronic Structure Calculationsmentioning
confidence: 99%
“…While there has been a large number of studies devoted to study these systems, they have predominantly focused on dimers. [2][3][4][5][6][7][8][9][10][11][13][14][15][16][17][18][20][21][22][25][26][27] The most extensively studied radical cation cluster is (H 2 O) 2 . + , and a wide variety of methods have been applied to characterise its structure.…”
Section: Introductionmentioning
confidence: 99%